2017
DOI: 10.1186/s12884-017-1430-5
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of external cephalic version for term breech presentation: an Australian population study, 2002–2012

Abstract: BackgroundThe safety, efficacy, and cost-effectiveness of external cephalic version (ECV) for term breech presentation has been demonstrated. Clinical guidelines recommend ECV for all eligible women, but the uptake of this procedure in the Australian healthcare setting is unknown. This study aimed to describe ECV uptake in New South Wales, the most populous state of Australia, during 2002 to 2012.MethodsData from routine hospital and birth records were used to identify ECVs conducted at ≥36 weeks’ gestation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…Criteria for suitability for ECV are poorly established, and our exclusion criteria for ECV were less conservative than those used in other studies . In addition, ECV acceptance among the population of the study was high (89.8%) …”
Section: Discussionsupporting
confidence: 82%
“…Criteria for suitability for ECV are poorly established, and our exclusion criteria for ECV were less conservative than those used in other studies . In addition, ECV acceptance among the population of the study was high (89.8%) …”
Section: Discussionsupporting
confidence: 82%
“…The same reasons were found in studies conducted in Australia and Korea. 17,18 26% opted to manage the situation by ECV the reasons for choosing this option were that apart from considering it safe they consider themselves expert in performing the procedure and managing the complication if it arises. A study done in Ireland which concluded the 10-year review on ECV also showed that it's a safe procedure and when performed by the operator who has performed 20 procedures the success rate of procedure is high.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were more morbidly obese women in the group of eligible women who did not undergo ECV compared with the eligible women that underwent ECV. 35 Therefore, the obese women available in this analysis may have been motivated to receive an ECV and may have had multiple attempts at ECV, leading to a higher success rate. However, among the women who underwent an attempt, we do not expect a systematic difference in the way an ECV was performed for an obese patient with a prior cesarean delivery compared with a normal weight patient with a prior cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%